Are Octogenarians at Higher Risk of Complications After Elective Lumbar Spinal Fusion Surgery? Analysis of a Cohort of 7880 Patients From the Kaiser Permanente Spine Registry. Issue 24 (15th December 2022) - Kuo, Calvin C.; Royse, Kathryn E.; Prentice, Heather A.; Harris, Jessica E.; Guppy, Kern H.
Abstract : Study Design: A retrospective cohort study with chart review. Objective: To determine if there is a difference in risk of adverse outcomes following elective posterior instrumented lumbar spinal fusions for patients aged 80 years and above compared with patients aged 50 to 79 years. Summary of Background Data: Patients aged 80 years and above are undergoing elective lumbar spinal fusion surgery in increasing numbers. There are conflicting data on the risks of intraoperative and postoperative complications in these patients. Materials and Methods: Patients aged 80 years and above were compared with 50 to 79 years (reference group) using time-dependent multivariable Cox proportional hazards regression with a competing risk of death for longitudinal outcomes and multivariable logistic regression for binary outcomes. Outcome measures used were: (1) intraoperative complications (durotomy), (2) postoperative complications: 30-day outcomes (pneumonia); 90-day outcomes (deep vein thrombosis, pulmonary embolism, emergency room visits, readmission, reoperations, and mortality); and two-year outcomes (reoperations and mortality). Results: The cohort consisted of 7880 patients who underwent primary elective posterior instrumented lumbar spinal fusion (L1–S1) for degenerative disk disease or spondylolisthesis. This was subdivided into 596 patients were aged 80 years and above and 7284 patients aged 50 to 79. After adjustment, patients aged 80 years and above had a higher likelihood of durotomy [odds ratio (OR)=1.43, 95% confidence interval (CI)=1.02–2.02] and 30-day pneumonia (OR=1.81, 95% CI=1.01–3.23). However, there was a lower risk of reoperation within two years of the index procedure (hazard ratio=0.69, 95% CI=0.48–0.99). No differences were observed for mortality, readmissions, emergency room visits, pulmonary embolism, or deep vein thrombosis. Conclusions: In a cohort of 7880 elective posterior instrumented lumbar fusion patients for degenerative disk disease or spondylolisthesis, we did not observe any significant risks of adverse events between patients aged 80 years and above and those aged 50 to 79 except for higher durotomies and 30-day pneumonia in the former. We believe octogenarians can safely undergo lumbar fusions, but proper preoperative screening is necessary to reduce the risks of 30-day pneumonia.